Answer:
Yes
Step-by-step explanation:
Answer:
Step-by-step explanation:
x y = 4^x (x, y)
-2 1/16 (-2, 1/16)
-1 1/4 (-1, 1/4)
0 1 (0, 1)
1 4 1, 4
3 64 3, 64
5 1024 (5, 1024)
Answer:
x=9
Step-by-step explanation:
(9-7) = 2
9 times 2 = 18 square feet
Amir can run 0.25 kilometers per minute.
Answer:
<u>Question 1</u>
The function
is one-to-one, so it does have an inverse.
The inverse of +6 is -6, so ![f^{-1}(x)=x-6](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dx-6)
Therefore, g(x) is the inverse of f(x).
<u>Question 2</u>
The function
is one-to-one, so it does have an inverse.
To find the inverse, replace f(x) with y:
![\implies y = -3x -9](https://tex.z-dn.net/?f=%5Cimplies%20y%20%3D%20-3x%20-9)
Rearrange the equation to make x the subject:
![\implies y+9= -3x](https://tex.z-dn.net/?f=%5Cimplies%20y%2B9%3D%20-3x)
![\implies x=-\dfrac13(y+9)](https://tex.z-dn.net/?f=%5Cimplies%20x%3D-%5Cdfrac13%28y%2B9%29)
![\implies x=-\dfrac13y-3](https://tex.z-dn.net/?f=%5Cimplies%20x%3D-%5Cdfrac13y-3)
Replace x with
and y with x:
![\implies f^{-1}(x)=-\dfrac13x-3](https://tex.z-dn.net/?f=%5Cimplies%20f%5E%7B-1%7D%28x%29%3D-%5Cdfrac13x-3)
Therefore, g(x) is the inverse of f(x).